Roles of Bile Acid-Activated Receptors in Monocytes-Macrophages and Dendritic Cells - Huilin Jia; Xingli He; Tengfei Jiang; Fanzhi Kong (Cells)
Bile acids (BAs), essential for lipid metabolism and fat-soluble vitamin absorption, also act as signaling molecules that regulate immune homeostasis. This review focuses on the roles of four key BA-activated receptors, farnesoid X receptor (FXR), G protein-coupled bile acid receptor 1 (GPBAR1), liver X receptors (LXRs), and vitamin D receptor (VDR), in modulating the functions of monocytes-macrophages, and dendritic cells (DCs). The biological synthesis, transport, and metabolism of BAs were discussed and highlighted the feedback mechanisms regulating the synthesis and enterohepatic circulation of BAs. Each receptor’s role in shaping immune responses is detailed, including their function in inflammation, apoptosis, phagocytosis, and pathogen clearance. FXR and GPBAR1 activation generally exhibits anti-inflammatory effects, while LXR and VDR modulate a more nuanced interplay between immune responses and lipid homeostasis. We also explored the cross-talk between BA-activated receptors and Toll-like receptors, providing a comprehensive understanding of the complex interplay between BA signaling and innate immunity. This review culminates by highlighting the therapeutic potential of targeting these receptors for the treatment of inflammatory and autoimmune diseases.